Security Threats In The Humanitarian Crisis In Ethiopia - Yudha Sabriansyah Sidiq; Uni Wahyuni Sagena (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
This study aims to explain the security threats in the humanitarian crisis in Ethiopia from 2020 to 2023, this study is a descriptive study. The data of this study uses data collection techniques in the nature of library research. Qualitative data analysis is the method used. The results of this study indicate that the conflict in Ethiopia caused a humanitarian crisis. From the study reviewed using the concept of Human Security because to analyze the threat of war crimes which are divided into: security in the fields of economy, food, health, environment, and security for individuals.